2007
DOI: 10.1111/j.1600-6143.2007.01793.x
|View full text |Cite
|
Sign up to set email alerts
|

Insurability of Living Organ Donors: A Systematic Review

Abstract: Being an organ donor may affect one's ability to obtain life, disability and health insurance. We conducted a systematic review to determine if insurability is affected by living organ donation, and if concern about insurability affects donor decision making. We searched MEDLINE, EMBASE, SCI, EconLit and Cochrane databases for articles in any language, and reviewed reference lists from 1966 until June 2006. All studies discussing the insurability of living organ donors or its impact on donor decision making we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 59 publications
0
33
0
Order By: Relevance
“…Outcomes for living kidney donors, such as perioperative complications, [12][13][14] psychosocial health, [15][16][17] and economic and insurability consequences, [18][19][20][21] are described elsewhere, as are outcomes for kidney recipients in relation to donor characteristics. 22,23 In this Review, we summarize studies that examine long-term medical outcomes for living kidney donors within the decade after donation, focusing on outcomes that can plausibly be associ ated with a reduction in GFR.…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes for living kidney donors, such as perioperative complications, [12][13][14] psychosocial health, [15][16][17] and economic and insurability consequences, [18][19][20][21] are described elsewhere, as are outcomes for kidney recipients in relation to donor characteristics. 22,23 In this Review, we summarize studies that examine long-term medical outcomes for living kidney donors within the decade after donation, focusing on outcomes that can plausibly be associ ated with a reduction in GFR.…”
Section: Introductionmentioning
confidence: 99%
“…All medically eligible patients can have access to an organ regardless of their financial circumstances. Furthermore, potential donors in a nationally funded health care system will have access to free health care post operatively and well beyond, and should not, following their act of kindness, be subject to encountering any difficulty in securing medical insurance which can be the case in the absence of a national health care system [46].…”
Section: An Important Feature: a National Health Care Systemmentioning
confidence: 99%
“…There (12) found that almost all insurance companies would provide life and health insurance to living organ donors, usually with no higher premiums. However, concern about insurability was still expressed by 2-14% of living organ donors in follow-up studies, and 3-11% of donors actually encountered difficulties with their insurance.…”
Section: Why Do Donors Need Long-term Medical Insurance?mentioning
confidence: 99%